Floating Point Multiplication Based on Schonhage Strassen Algorithm - Srikanth, B; Siva Kumar, M; Hari Kishore, K (International Journal of Engineering and Technology, 2018)
In this paper, the single precision float point multiplication is performed using the Schonhage Strassen Algorithm. There are several types of floating point multiplications like Karatsubha and Toom cook. The Schonhage Strassen algorithm is conventionally a fixed point integer multiplication algorithm. The main advantage of the Schonhage Strassen multiplication is that, the multiplication of integer values greater than 5 digits ranging from 2215 to 2217 bit values proves to be efficient. The validation of the proposed floating point multiplication is done using FPGA real time implementation. The analysis of parameters like area and power are evaluated.Â Â